1978
DOI: 10.1002/1097-0142(197804)41:4<1538::aid-cncr2820410443>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous cystadenoma, serous cystadenoma and benign cystic teratoma of the ovary.Clinico-pathologic differences observed in a Malaysian hospital

Abstract: A study of 207 benign ovarian tumors seen at the University Hospital, Kuala Lumpur between 1968 and 1975 was made to evaluate the clinical features that might be useful in the preoperative differentiation of mucinous cystadenoma, serous cystadenoma, and cystic teratoma of the ovary. This study indicated that the pertinent information included the mean age of the patient, the marital and menstrual status, and the estimated tumor size. The racial background was an additional factor in serous cystadenoma. Featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…In contrast to previous reports suggesting a predisposition of ovarian dermoid cysts to a right lateral distribution [2][3][4], this study found that there is no significant difference in the lateral distribution of this type of cysts. Our findings, however, support the reports that ovarian endometriomas are more common in the left than in the right ovary.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous reports suggesting a predisposition of ovarian dermoid cysts to a right lateral distribution [2][3][4], this study found that there is no significant difference in the lateral distribution of this type of cysts. Our findings, however, support the reports that ovarian endometriomas are more common in the left than in the right ovary.…”
contrasting
confidence: 99%
“…
Previous studies have suggested that the proportion of left ovarian endometriotic cysts is significantly higher than the expected 50% [1], but that ovarian dermoid cysts have a predisposition to a right lateral distribution [2][3][4].We studied the distribution of benign ovarian cysts in 1184 consecutive women undergoing surgery at our institution between August 1994 and December 2003. Information was abstracted from a continuously updated database.
…”
mentioning
confidence: 99%
See 1 more Smart Citation